2020
DOI: 10.1155/2020/2084646
|View full text |Cite
|
Sign up to set email alerts
|

Steel Fibre Reinforced Concrete Meso‐Scale Numerical Analysis

Abstract: Concrete is a heterogeneous composite consisting of aggregate, cement paste, and void. Steel fibre reinforced concrete (SFRC) has been widely studied experimentally and numerically in recent decades. The fibre geometry model program generated by a secondary development ANSYS program was exported to midas FEA for analysis. The constitutive concrete model adopts the total strain crack model of concrete. A steel fibre bond slip is considered in an equivalent manner using the von Mises model. The results of the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…A procedure written in GNU OCTAVE and LISP, similar to the method described in the publication [ 43 ], was used for random fiber generation. The number of fibers was determined based on the fiber content in the amount of in a volume of 500 × 200 × 50 mm.…”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A procedure written in GNU OCTAVE and LISP, similar to the method described in the publication [ 43 ], was used for random fiber generation. The number of fibers was determined based on the fiber content in the amount of in a volume of 500 × 200 × 50 mm.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…The parabolic total strain crack model [ 42 , 43 ] represents another group of continuous mechanics approaches based on a fuzzy attempt to fracture energy. It is used in the analysis of concrete structures, assuming concrete as a non-linear, isotropic, homogeneous material.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has been conducted on the effect of steel fiber on concrete performance owing to the good performance of SFRC. It has been demonstrated that integrating steel fiber into concrete can improve compressive strength, the elastic modulus, and flexural strength [9][10][11][12]. Abbass et al [13] investigated the effect of steel fibers with different lengths and diameters on the mechanical properties of concrete.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of existing research focused on the influence of different lengths, aspects, and shapes of steel fibers on the mechanical properties of concrete (e.g., [9][10][11][12][13][14][15][16][17][18]), the appropriate content of steel fiber (e.g., [19]), and the ratio of steel fiber length and aggregate size (e.g., [21][22][23]). Meanwhile, studies on the application of SFRC in tunnel linings have mainly focused on the structural form and design method of SFRC single-layer linings (e.g., [24][25][26]), as well as the effect of SFRC on the bearing capacity and toughness of the lining (e.g., [27][28][29][30][31][32][33]).…”
Section: Introductionmentioning
confidence: 99%